A graphene lithium battery composite material and preparation method thereof

By modifying graphene and combining polyvinyl alcohol and acrylamide, the problems of instability and low energy density of graphene in lithium battery applications are solved, and higher cycle stability and energy density are achieved.

CN115763754BActive Publication Date: 2025-04-18HUNAN JINYANG ALKENE CARBON NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211515300.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-04-18
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

The existing graphene has problems of instability and low volume energy density in lithium battery applications, which limits its application to better exert its characteristics.

Method used

By using double transition metal oxide to modify graphene and combining polyvinyl alcohol and acrylamide, the compatibility and dispersion of graphene are improved, and its electrochemical properties and cyclic stability are improved.

Benefits of technology

It improves the cyclic stability and capacitance of graphene lithium battery composite materials, enhances the conductivity and energy density, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003971715530000061
    Figure BDA0003971715530000061
Patent Text Reader

Abstract

The present invention discloses a graphene lithium battery composite material and a preparation method thereof, comprising the following components calculated by weight: 40-60 parts of electrode material, 35-45 parts of modified graphene; 28-36 parts of polyvinyl alcohol, 2-6 parts of acrylamide, and 70-100 parts of solvent; the modified graphene is modified by double transition metal oxide. On the one hand, the present invention uses polyvinyl alcohol and acrylamide to improve the compatibility and dispersibility of graphene. On the other hand, the introduction of double transition metals into the graphene modified by double transition metal oxide can produce synergistic effects between the double transition metals, resulting in changes in the electronic structure, thereby improving the electrochemical properties of graphene, and improving the conductivity and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a graphene lithium battery composite material and a preparation method thereof. Background Art

[0002] After entering the 21st century, various electronic products (such as smart phones, iPads, laptops and digital cameras) and electric vehicles (such as electric bicycles, electric cars and hybrid cars) have become daily necessities in people's lives. While they bring convenience to people's lives, they also put forward higher requirements for batteries, such as small and light weight, large storage capacity, long service life, good safety, and fast charging and discharging. At present, lead-acid, nickel-cadmium and nickel-metal hydride batteries have been used in electronic products and electric vehicles, but because of their large size, easy to pollute the environment, short service life and low energy density, they are difficult to be used in electric vehicles on a large scale. As a new type of high-energy secondary power source, lithium-ion secondary batteries have the advantages of large specific energy, stable discharge voltage, high voltage, good low-temperature performance, no pollution, superior safety performance, long storage and working life, and high utilization rate.

[0003] Graphene has excellent optical, electrical and mechanical properties, and has important application prospects in materials science, micro-nano processing, energy, biomedicine and drug delivery. The characteristics of graphene make it have broad application prospects in the field of lithium batteries, but graphene has problems such as instability and low volume energy density during use, which limits graphene from better exerting its characteristics. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the first aspect of the present invention provides a graphene lithium battery composite material, which can effectively improve the cycle stability and capacity.

[0005] The second aspect of the present invention also provides a method for preparing a graphene lithium battery composite material.

[0006] A graphene lithium battery composite material according to the first aspect of the present invention comprises the following components calculated by weight:

[0007] 40-60 parts of electrode material, 35-45 parts of modified graphene; 28-36 parts of polyvinyl alcohol, 2-6 parts of acrylamide, 70-100 parts of solvent;

[0008] The modified graphene is modified by double transition metal oxides.

[0009] The graphene lithium battery composite material according to the embodiment of the present invention has at least the following beneficial effects:

[0010] On the one hand, the present invention uses polyvinyl alcohol and acrylamide to improve the compatibility and dispersibility of graphene. On the other hand, the introduction of double transition metals into graphene modified by double transition metal oxides can produce a synergistic effect between the double transition metals, leading to a change in the electronic structure, thereby improving the electrochemical properties of graphene, and improving the conductivity and cycle stability.

[0011] According to some embodiments of the present invention, the chemical formula of the double transition metal oxide is MCo2O4; the M is selected from one of Mn, Fe, and Ni. There is a strong hybridization between the M metal and the oxygen in MCo2O4 near the Fermi level, which is conducive to electron transfer and enhances the conductivity.

[0012] According to some embodiments of the present invention, the chemical formula of the double transition metal oxide is FeCo2O4. The energy density is further improved because the hybridization between the iron element and Co greatly increases the quantum capacitance value of the system, thereby increasing its energy density.

[0013] According to some embodiments of the present invention, the electrode material is selected from one of LiCl, LiBr, Li2SO4 or LiNO3.

[0014] According to some embodiments of the present invention, the solvent is selected from at least one of polyethylene glycol, ethanol or ethyl acetate.

[0015] According to some embodiments of the present invention, the method for preparing the double transition metal oxide comprises the following steps:

[0016] S110, mixing a metal salt and cobalt nitrate to obtain a first mixed solution;

[0017] S120, mixing the treated nickel foam, the first mixed solution and oxalic acid, and performing a hydrothermal reaction to obtain a first product;

[0018] S130, calcining the first product to obtain a double transition metal oxide.

[0019] According to some embodiments of the present invention, the temperature of the hydrothermal reaction is 90-120°C.

[0020] According to some embodiments of the present invention, the hydrothermal reaction time is 1 to 10 hours.

[0021] According to some embodiments of the present invention, the calcination temperature is 350-500°C.

[0022] According to some embodiments of the present invention, the calcination time is 1 to 6 hours.

[0023] According to some embodiments of the present invention, the metal salt is one of iron nitrate, lithium nitrate and manganese nitrate.

[0024] According to some embodiments of the present invention, the method for preparing modified graphene comprises the following steps:

[0025] S310, dissolving the prepared double transition metal oxide and graphene in a solvent, dispersing by ultrasonication, and drying to obtain a solid mixture;

[0026] S320, calcining the solid mixture under an inert atmosphere to obtain modified graphene.

[0027] According to a second aspect of the present invention, an embodiment provides a method for preparing a graphene lithium battery composite material, comprising the following steps:

[0028] S210, ultrasonically dispersing the modified graphene, polyvinyl alcohol, acrylamide and part of the solvent to obtain a mixed solution;

[0029] S220, ultrasonically mixing the mixed solution, the electrode material and the remaining solvent to obtain a precursor;

[0030] S230, electrospinning the precursor, and then drying to obtain a graphene lithium battery composite material.

[0031] According to some embodiments of the present invention, the electrospinning is performed under the conditions of a flow rate of 0.5-2 mL / h, a voltage of 15-25 KV, and a needle diameter of 0.1 mm-1.0 mm.

[0032] According to some embodiments of the present invention, the frequency of the ultrasound is 40-60 KHZ.

[0033] According to some embodiments of the present invention, in step S230, the drying temperature is 60-80°C.

[0034] According to some embodiments of the present invention, in step S230, the drying time is 24 to 48 hours.

[0035] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be obvious from the description, or may be learned by practice of the present invention. DETAILED DESCRIPTION

[0036] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0037] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0038] Example 1

[0039] Embodiment 1 provides a graphene lithium battery composite material, comprising the following steps:

[0040] The double transition metal oxide FeCo2O4 is prepared by the following steps:

[0041] S110, dissolving 1 mmol of ferric nitrate and 2 mmol of cobalt nitrate in water and mixing to obtain a first mixed solution;

[0042] S120, mixing the treated nickel foam, the first mixed solution and oxalic acid, and performing a hydrothermal reaction at 100° C. for 2 h to obtain a first product;

[0043] S130, calcining the first product at 400°C for 2h with a heating rate of 2°C / min to obtain the double transition metal oxide FeCo2O4.

[0044] The steps for preparing modified graphene are as follows:

[0045] S310, weighing the prepared double transition metal oxide FeCo2O4 and graphene in a mass ratio of 1:8, dissolving them in anhydrous ethanol, ultrasonically dispersing them, and drying them at 80° C. to obtain a solid mixture;

[0046] S320, calcining the solid mixture at 500° C. under a nitrogen atmosphere for 5 hours to obtain modified graphene.

[0047] The amount of graphene lithium battery composite material is shown in Table 1. The preparation method thereof comprises the following steps:

[0048] S210, ultrasonically dispersing the modified graphene, polyvinyl alcohol, acrylamide and part of the solvent at a frequency of 50 KHZ for 45 minutes to obtain a mixed solution;

[0049] S220, ultrasonically mixing the mixed solution, the electrode material and the remaining solvent to obtain a precursor;

[0050] S230, delivering the above precursor into a syringe, performing electrospinning under the conditions of a flow rate of 1 mL / h, a voltage of 20 KV and a needle diameter of 0.5 mm, and then drying at a temperature of 60° C. for 38 h to obtain a graphene lithium battery composite material.

[0051] Example 2

[0052] Embodiment 2 provides a graphene lithium battery composite material, comprising the following steps:

[0053] The double transition metal oxide MnCo2O4 is prepared by the following steps:

[0054] S110, dissolving 1 mmol of manganese nitrate and 2 mmol of cobalt nitrate in water and mixing to obtain a first mixed solution;

[0055] S120, mixing the treated nickel foam, the first mixed solution and oxalic acid, and performing a hydrothermal reaction at 100° C. for 2 h to obtain a first product;

[0056] S130, calcining the first product at 400°C for 2h with a heating rate of 2°C / min to obtain the double transition metal oxide MnCo2O4.

[0057] The steps for preparing modified graphene are as follows:

[0058] S310, weighing the prepared double transition metal oxide MnCo2O4 and graphene in a mass ratio of 1:8, dissolving them in anhydrous ethanol, ultrasonically dispersing them, and drying them at 80° C. to obtain a solid mixture;

[0059] S320, calcining the solid mixture at 500° C. under a nitrogen atmosphere for 5 hours to obtain modified graphene.

[0060] The amount of graphene lithium battery composite material is shown in Table 1. The preparation method thereof comprises the following steps:

[0061] S210, ultrasonically dispersing the modified graphene, polyvinyl alcohol, acrylamide and part of the solvent at a frequency of 50 KHZ for 45 minutes to obtain a mixed solution;

[0062] S220, ultrasonically mixing the mixed solution, the electrode material and the remaining solvent to obtain a precursor;

[0063] S230, delivering the above precursor into a syringe, performing electrospinning under the conditions of a flow rate of 1 mL / h, a voltage of 20 KV and a needle diameter of 0.5 mm, and then drying at a temperature of 60° C. for 38 h to obtain a graphene lithium battery composite material.

[0064] Example 3

[0065] Embodiment 3 provides a graphene lithium battery composite material, comprising the following steps:

[0066] Preparation of double transition metal oxide NiCo2O4, the steps are as follows:

[0067] S110, dissolving 1 mmol of nickel nitrate and 2 mmol of cobalt nitrate in water and mixing to obtain a first mixed solution;

[0068] S120, mixing the treated nickel foam, the first mixed solution and oxalic acid, and performing a hydrothermal reaction at 100° C. for 2 h to obtain a first product;

[0069] S130, calcining the first product at 400°C for 2h with a heating rate of 2°C / min to obtain double transition metal oxide NiCo2O4.

[0070] The steps for preparing modified graphene are as follows:

[0071] S310, weighing the prepared double transition metal oxide NiCo2O4 and graphene in a mass ratio of 1:8, dissolving them in anhydrous ethanol, ultrasonically dispersing them, and drying them at 80° C. to obtain a solid mixture;

[0072] S320, calcining the solid mixture at 500° C. under a nitrogen atmosphere for 5 hours to obtain modified graphene.

[0073] The amount of graphene lithium battery composite material is shown in Table 1. The preparation method thereof comprises the following steps:

[0074] S210, ultrasonically dispersing the modified graphene, polyvinyl alcohol, acrylamide and part of the solvent at a frequency of 50 KHZ for 45 minutes to obtain a mixed solution;

[0075] S220, ultrasonically mixing the mixed solution, the electrode material and the remaining solvent to obtain a precursor;

[0076] S230, delivering the above precursor into a syringe, performing electrospinning under the conditions of a flow rate of 1 mL / h, a voltage of 20 KV and a needle diameter of 0.5 mm, and then drying at a temperature of 60° C. for 38 h to obtain a graphene lithium battery composite material.

[0077] Example 4

[0078] Example 4 provides a graphene lithium battery composite material, and its preparation method is the same as that of Example 1, except that the amount of components is used, see Table 1.

[0079] Example 5

[0080] Example 5 provides a graphene lithium battery composite material, and its preparation method is the same as that of Example 1, except that the amount of components is used, see Table 1.

[0081] Table 1 Examples 1 to 5

[0082] Example 1 Example 2 Example 3 Example 4 Example 5 <![CDATA[Electrode material / LiNO3]]> 50 50 50 40 60 Modified graphene 40 40 40 45 35 Polyvinyl alcohol 30 30 30 28 36 Acrylamide 4 4 4 6 2 Solvents 80 80 80 70 100

[0083] Comparative Example 1

[0084] Comparative Example 1 provides a graphene lithium battery composite material, the preparation method and dosage are the same as those in Example 1, except that graphene is used instead of modified graphene.

[0085] Comparative Example 2

[0086] Comparative Example 2 provides a graphene composite material, and the preparation steps are as follows:

[0087] The steps for preparing modified graphene are as follows:

[0088] S310, weighing double transition metal oxide Co3O4 and graphene in a mass ratio of 1:8, dissolving them in anhydrous ethanol, ultrasonically dispersing them, and drying them at 80° C. to obtain a solid mixture;

[0089] S320, calcining the solid mixture at 500° C. under a nitrogen atmosphere for 5 hours to obtain modified graphene.

[0090] The amount of the graphene lithium battery composite material is the same as that in Example 1, and the preparation method thereof comprises the following steps:

[0091] S210, ultrasonically dispersing the modified graphene, polyvinyl alcohol, acrylamide and part of the solvent at a frequency of 50 KHZ for 45 minutes to obtain a mixed solution;

[0092] S220, ultrasonically mixing the mixed solution, the electrode material and the remaining solvent to obtain a precursor;

[0093] S230, delivering the above precursor into a syringe, performing electrospinning under the conditions of a flow rate of 1 mL / h, a voltage of 20 KV and a needle diameter of 0.5 mm, and then drying at a temperature of 60° C. for 38 h to obtain a graphene lithium battery composite material.

[0094] Performance Testing

[0095] The graphene lithium battery composite materials obtained in Examples 1 to 5 and Comparative Examples 1 to 2 were made into soft-package lithium-ion batteries according to a conventional method, and the charge and discharge performance tests were carried out under the condition of a current density of 50 mA / g, and the charge and discharge voltage range was 0.1 to 2.0 V. The battery's initial discharge capacity and the discharge capacity after 300 cycles were measured. The test results are shown in Table 2.

[0096] Table 2 Electrical properties of Examples 1 to 5 and Comparative Examples 1 to 2

[0097]

[0098] From Examples 1 to 5 and Comparative Examples 1 to 2, the present application can effectively improve the conductivity, energy density and cycle stability by modifying graphene through double transition metal oxides. From Examples 1 to 3, when the double transition metal oxide is FeCo2O4, its energy density is the highest and the effect is the best.

[0099] Since the comparative examples 1 and 2 are graphenes that have not been modified or have been modified with cobalt tetroxide, their effects are worse than those of the embodiments of the present application.

[0100] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A graphene lithium battery composite material, characterized in that: The composition comprises the following components calculated by weight: 40-60 parts of electrode material, 35-45 parts of modified graphene; 28-36 parts of polyvinyl alcohol, 2-6 parts of acrylamide, 70-100 parts of solvent; The modified graphene is modified by a double transition metal oxide; the chemical formula of the double transition metal oxide is MCo2O4; the M is selected from one of Mn, Fe and Ni; The preparation method of the double transition metal oxide comprises the following steps: S110, mixing a metal salt and cobalt nitrate to obtain a first mixed solution; S120, mixing the treated nickel foam, the first mixed solution and oxalic acid, and performing a hydrothermal reaction to obtain a first product; S130, calcining the first product to obtain a double transition metal oxide; The preparation method of the modified graphene comprises the following steps: S310, dissolving the prepared double transition metal oxide and graphene in a solvent, dispersing by ultrasonication, and drying to obtain a solid mixture; S320, calcining the solid mixture under an inert atmosphere to obtain modified graphene.

2. The graphene lithium battery composite material according to claim 1, characterized in that: The chemical formula of the double transition metal oxide is FeCo2O4.

3. The graphene lithium battery composite material according to claim 1, characterized in that: The electrode material is selected from one of LiCl, LiBr, Li2SO4 or LiNO3.

4. The graphene lithium battery composite material according to claim 1, characterized in that: The solvent is selected from at least one of polyethylene glycol, ethanol or ethyl acetate.

5. The graphene lithium battery composite material according to claim 4, characterized in that: The temperature of the hydrothermal reaction is 90-120°C.

6. The graphene lithium battery composite material according to claim 4, characterized in that: The calcination temperature is 350-500°C.

7. The method for preparing a graphene lithium battery composite material according to any one of claims 1 to 6, characterized in that: The steps include: S210, ultrasonically dispersing the modified graphene, polyvinyl alcohol, acrylamide and part of the solvent to obtain a mixed solution; S220, ultrasonically mixing the mixed solution, the electrode material and the remaining solvent to obtain a precursor; S230, electrospinning the precursor, and then drying to obtain a graphene lithium battery composite material.

8. The method for preparing the graphene lithium battery composite material according to claim 7, characterized in that: The electrospinning is carried out under the conditions of a flow rate of 0.5-2 mL / h, a voltage of 15-25 KV and a needle diameter of 0.1 mm-1.0 mm.

Citation Information

Patent Citations

  • Method for preparing graphene composite nanometer fiber material by electrostatic spinning

    CN109616615A

  • Graphene lithium battery composite material and preparation method

    CN112151785A

  • Three-dimensional composites of nickel cobalt oxide / graphene on nickel foam for supercapacitor electrodes, and preparation method thereof

    US20170053750A1